Sisham trees planted with gram in semi-arid agriculture can yield profit - Gill, A S; Singh, Ram Ashray (Indian Farming, 2015)
On the basis of five-year field study (1999-2004) under rainfed agroforestry system in the semi-arid subtropics conditions, the results have shown that highest net benefit returns was recorded with sole planting of chickpea but the highest profit was achieved with a combination of Sisham tree (Dalbergia sissoo) with gram crop (Cicer arietinum). The marginal loss in chickpea production in association with the tree component was compensated with the tree yield (fodder and fuel) due to pruning.